Low inhibition of alpha-glucosidase and xanthine oxidase activities of ethanol extract of Momordica charantia fruit - Khatib, Alfi; Perumal, Vikneswari; Ahmed, Qamar Uddin; Uzir, Bisha Fathamah; Murugesu, S (Wolters Kluwer - Medknow Publications Wolters Kluwer India Pvt. Ltd., 2017)
Objective: To evaluate the α-glucosidase and xanthine oxidase inhibitory activities of different ethanolic and aqueous extracts of Momordica charantia fruit. Materials and Methods: The M. charantia fruits were extracted using different concentrations of ethanol in water (0, 20, 40, 60, 80 and 100 %, v/v). The samples from different ethanolic and aqueous extracts of M. charantia fruit (0, 20, 40, 60 and 100 % ethanol in water [v/v] extracts) were tested for α-glucosidase and xanthine oxidase inhibitory activities. Quercetin and allopurinol were used as positive controls for α-glucosidase and xanthine oxidase inhibitory assay, respectively. The samples were also tested for phytochemicals screening such as alkaloid, phenol, steroid, tannin, coumarins and flavonoid. The significant difference was determined by one-way ANOVA test with a Tukey comparison at confidence interval of 95%. Results: Phytochemical screening showed the presence of coumarin, alkaloid, steroid and phenol in the extracts. The six different M. charantia extracts showed low inhibition on α-glucosidase and xanthine oxidase activities. Conclusions: The antidiabetic activity of the ethanolic and aqueous extracts of M. charantia fruit was not through the inhibition of α-glucosidase and xanthine oxidase.